2017
DOI: 10.1534/genetics.116.194688
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Landrace Genome Diversity

Abstract: Understanding the genomic complexity of bread wheat is important for unraveling domestication processes, environmental adaptation, and for future of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 62 publications
3
85
0
Order By: Relevance
“…Here, we developed a spring wheat NAM population and used it to dissect the genetic architecture of recombination rate variation, and to study the relationship between recombination, genetic variation, and deleterious SNPs in an allopolyploid crop with a large, highly repetitive genome. This NAM population further expands the number of multi‐parent mapping populations available to the wheat community for studying the genetic architecture of complex traits (Cavanagh et al ., ; Bajgain et al ., ; Gardner et al ., ; Wingen et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we developed a spring wheat NAM population and used it to dissect the genetic architecture of recombination rate variation, and to study the relationship between recombination, genetic variation, and deleterious SNPs in an allopolyploid crop with a large, highly repetitive genome. This NAM population further expands the number of multi‐parent mapping populations available to the wheat community for studying the genetic architecture of complex traits (Cavanagh et al ., ; Bajgain et al ., ; Gardner et al ., ; Wingen et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…While these findings hold great promise for plant breeding, their practical applications are hindered by the limited understanding of the genetics of recombination rate control in specific crops that may differ in genomic organization, genome size, or ploidy level from those of the model species (Mercier et al ., ). For example, some of the most important agricultural crops, like wheat, maize, or barley contain large regions of the genome comprised of transposable elements, preferentially located in the pericentromeric regions, in which recombination is severely suppressed (Akhunov et al ., ; Saintenac et al ., ; Choulet et al ., ; Wingen et al ., ). Due to the reduced efficiency of background selection, these genomes were shown to be enriched for SNPs with possible deleterious effects (Mezmouk and Ross‐Ibarra, ; Liu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In this manner, rather than phenotyping a large diversity collection for many traits, the phenotypic value of different haplotype blocks across a specific interval could be examined in further detail. The Watkins nested association mapping populations offer a valuable resource to this effect as the landrace haplotypes can be directly evaluated within available mapping populations (Wingen et al ., ). As breeding programs increasingly look to combine genotypic and phenotypic data, the availability of haplotype data for wild relatives, landrace collections and elite wheat cultivars with their associated phenotypic value has the potential to shape the way in which breeding programs are structured.…”
Section: Moving From Snps To Haplotypes In Breedingmentioning
confidence: 97%
“…Recent genetic studies have shown the potential for these wild species to provide useful genetic variation for grain weight that could possibly have been excluded from the gene pool during domestication (Golan et al ; Arora et al ; Avni et al ). The genome sequences and other genomic resources now available for many of these progenitor species and landraces will aid the identification of these novel genes and alleles (Avni et al ; Luo et al ; Wingen et al ).…”
Section: Interactionsmentioning
confidence: 99%